Tuberculosis diagnosis after bleach processing for early stage tuberculosis laboratory capacity building - David, S.; Sutre, A. F.; Sanca, A.; Mane, A.; Henriques, V.; Portugal, C.; Sancho, L.; Cardoso, A.; Paixao, E.; Duarte, E. L.; Leite, Clarice Queico Fujimura [UNESP]; Salem, J. I.; et al. (Int Union Against Tuberculosis Lung Disease (i U A T L D), 2012)
The diagnosis of tuberculosis is seriously hampered in the absence of standard biosafety laboratory facilities for specimen concentration and Mycobacterium tuberculosis culture. Within a laboratory twinning arrangement, heat-fixed direct smear and sediment from 74 bleach-processed and 20 non-processed specimens from Cumura Hospital, Guinea-Bissau, were sent to Lisbon for molecular evaluation of rifampicin resistance. Sequence analysis of a 369 base-pair ppoB locus detected 3.2% (3/94) resistant specimens. To our knowledge, this represents the first report on the molecular analysis of M. tuberculosis from bleach-processed sputum, an alternative to current diagnostic practice in low-resource settings.
Keywords: Mycobacterium tuberculosis; rpoB; sputum smear microscopy; sodium hypochlorite; denaturing high-performance liquid chromatography (DHPLC) sequencing